Peran Latihan Rentang Gerak Aktif dalam Meningkatkan Toleransi Aktivitas Lansia: The Role of Active Range of Motion Exercises in Improving Activity Tolerance in the Elderly - Saraswati, Ayunda Putri; Nurhidayat, Saiful; Sari, Rika Maya (Journal of Health (JoH), 2025)
The elderly are vulnerable to experiencing various kinds of health problems. Increasing age causes some body performance to decline which can result in decreased physical activity in meeting activity needs. The ability to carry out activities cannot be separated from the adequacy of the musculoskeletal system which can result in activity intolerance nursing problems. The aim of this study was to determine the role of active range of motion exercises in increasing activity tolerance in the elderly. The research method applied was qualitative with a case study approach which set the target of 1 elderly person at UPT PSTW Magetan who experienced activity intolerance and was given active range of motion exercises. The results of the research obtained subjective data, namely that clients complained of getting tired quickly, feeling weak and uncomfortable after carrying out activities. The objective data obtained is that the client looks tired and blood pressure appears to increase when at rest. The nursing intervention used to overcome the problem is active range of motion exercises which aim to increase muscle strength and activity tolerance. Evaluation after giving the treatment for 6 days was that complaints of fatigue and weakness decreased, ease of carrying out activities increased, and blood pressure began to improve. In conclusion, active range of motion exercises are effective in improving muscle strength and activity tolerance in the elderly, and are recommended for independent practice.